Socioeconomic barriers to facility-based delivery in urban poor communities of Lagos: Wealth, linguistic capacity, and residential area - Yoshito Kawakatsu; Hirotsugu Aiga; Osy Ubani; Adefunke Oyeniyi Adesina; Sumihisa Honda; Junko Otaki; Nobuhiro Kadoi (Elsevier, 2020)
Background: The objective of this study is to describe delivery care utilizations and to identify socioeconomic barriers to practicing facility-based deliveries, in urban poor communities of Lagos, Nigeria. Methods: The study was a prospective cohort study conducted in Lagos Mainland, a local government area of Lagos State, Nigeria. A total of 723 randomly selected pregnant women participated in this study. The socio-economic barriers were sought from three different perspectives, i.e., household wealth as a financial barrier, linguistic capacity as a social barrier, and residential area as a physical barrier. The data were analyzed with descriptive and multivariate statistical methods using the imputed datasets. Results: While 41.9% of the participants delivered at governmental health facilities, 28.3% and 29.8% of them gave births at private health facilities and other places, respectively. As the results of the analyses, household wealth was positively associated with childbirth at a governmental health facility. Egun-speaking women were more likely to give births at private facilities than Yoruba-speaking women, while Igbo-speaking and Hausa-speaking women were more likely to choose other places for their childbirths. Conclusion: This study identified the financial and linguistic barriers to facility-based deliveries among women in urban poor communities.